Memprediksi Turnover Intention melalui Employee Motivation dan Employee Engagement di Hotel W Bali - Seminyak - Adrie Oktavio; Michelle Laurent; Verina Wijaya (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2020)
The rapid development of tourism industry raises a strong competition among hotels in Bali.  Hotels must be able to have strong competitiveness by maintaining and managing their assets, one of which is human resources or the employees, hence a special treatment is needed to maintain the loyalty to the company.  In other words, the hotel needs to retain its best employees so that the employee has no intention of leaving or turnover intention. The purpose of this study is to analyze to what extent the turnover intention variable is influenced by the employee motivation and employee engagement variables. It is a quantitative research that uses the GSCA (Generalized Structured Component Analysis) analysis method. The data in this study was obtained from a questionnaire distributed to 112 permanent employees of the W Bali - Seminyak Hotel with the criteria of at least one year working period. The results show that employee motivation has a positive and significant effect on employee engagement. However, employee motivation has a negative and significant effect on turnover intention. Employee engagement has a negative and significant effect on turnover intention, yet employee engagement mediates the relationship between employee motivation and turnover intention